دور الخدمة الاجتماعية في تعزيز الوعي البيئي وتأثيراته على صحة المجتمع العامة - أبو ديب, زينة ساسي الدهماني (مجلة الاصالة, 2025)
دور الخدمة الاجتماعية في تعزيز الوعي البيئي وتأثيراته على صحة المجتمع العامة